Design and development of a flexural spindle mechanism enabled in micro drilling machine tool within a PLM environment - Shinde, Sachin Manohar; Solanke, Sachin; Diwan, Mohit; Bhole, Kiran S.; Salunkhe, Sachin; Cep, Robert; Nasr, Emad Abouel (Frontiers in Mechanical Engineering, 2026)
The advent of designing flexural systems was to provide accurate micro and nano displacement between the assembly members of the mechanism. Applications that used these mechanisms included linear compressors, optomechanical devices, Stirling engines, cryocoolers, microcheck valves, Flexure-based Electromagnetic Linear actuators, and so on. This paper focuses on the machine-tool fabrication of a novel flexural mechanism encased within the spindle head of the microdrilling head. The mechanism cushioned the micro drill and protected it from permanent damage when encountering undeclared resistance in the material matrix. Furthermore, this paper focuses solely on building a 3-axis drilling machine tool in a Product Lifecycle Management environment. The study follows a systematized approach for validating the machine tool design, starting with the hierarchical assembly of components using various kinematic chains. The next phase involves assigning the necessary motions to these components. The final stage utilizes a virtual controller and post-processor to simulate and control machine tool movements. Validation is then performed on the simulated workpiece to ensure design accuracy and functionality. The key findings of the studies indicate that the designed mechanism can move in and out and can also puncture micro-holes in metal. This is the mechanism’s capability, which is the novelty.